Neutron reflection from hexadecyltrimethylammonium bromide adsorbed on smooth and rough silicon surfaces - Fragneto, G; Thomas, R; Rennie, A; Penfold, J (1996)
Neutron reflection has been used to investigate the structure of hexadecyltrimethylammonium bromide (C16TAB) layers adsorbed at the silicon/silicon oxide/aqueous interface. Separate isotopic labeling of groupe of four methylene groups at a time made it possible to determine the structure of the layer at a higher resolution than previously possible. The structure of the layer was investigated on smooth and rough surfaces. The roughness of the surface has a significant effect on the properties of the layer. On the rough surface the bilayer is shown to be thicker and to be unsymmetrical in the direction of the surface normal. The surface coverage was also found to be lower on the rough surface. As in previous studies the surface was found not to be completely covered, lending support to the idea that adsorption is in the form of aggregates. The division into smaller isotopically labeled fragmente shows, however, that the aggregates strongly resemble bilayer fragments, and their overall thickness, at 32 ± 1 Å, is substantially less than the diameter of a micelle.